(3GdeNGHQGJ h GdYGde (B:s (3GdLRA GdNGeS (B/s - (3GdLRGFQj, SYjOs ((3HjQhJ (B:s (3OGQ GdLjd ,s, 1997)
(3YedjI GUOGQ gPg GdcJH Ydi GLRGA NeSI ddeNGHQGJ h GdYGde h gPG GdLRA GNQgG h cGf cJGH eTGgjQ MQchG GdYGde bO UOQ HLRFg GdGhd h jUOQ GdLRA GdKGfj Vef HQfGeL GYOOJg NUjUG ceG SjUOQ cJGHGj GdJUajGJ GdSjGSjI aj GdYGde h eda GdJSYjfGJ h jJHY cdG efgeG LRDg GdKGfj aj hbJg dJJe GdeYQaI h GdGWdGY h QHW GdGehQ h GdGMOGK GdYGeI GdJj fLeYgG ef TJi GfMGA GdYGdes
Keywords: (3GdeNGHQGJ GdSjGSjIs; (3GdYGdes